Castanea sativa Mill. flowers amongst the most powerful antioxidant matrices: a phytochemical approach in decoctions and infusions - Carocho, Márcio (2014)
Infusions and decoction of chestnut tree flowers have been used for different medical purposes, but their phytochemical profile and antioxidant activity are still mostly unknown. Herein, decoctions and infusions of flowers from the two most appreciated chestnut cultivars (longal and judia) in Tr´as-os-Montes, Portugal, were prepared and characterized with regard to their content in free sugars, organic acids, and phenolic compounds, such as flavonoids and hydrolyzable tannins, and their antioxidant activity. Overall, the decoction of the cultivar judia was the sample with both the highest quantity of flavonoids and antioxidant activity. The phenolic compound with the highest abundance in all samples was trigalloyl-HHDP-glucoside, followed by pentagalloyl glucoside. The sample with the highest quantity of total phenolic compounds was judia infusion, closely followed by longal decoction, which also gave the highest quantities of ellagitannins. Regarding sugars and organic acids, the profiles were more similar. These results corroborate ancestral claims of the health benefits of infusions and decoctions of chestnut flowers